COLONIZERS IN THE NEIGHBORHOOD: A CONTENT ANALYSIS OF NEXTDOOR USERS’ “POSTRACIAL” SURVEILLANCE - Lee, Jenny; Ahn, Chloe (AoIR Selected Papers of Internet Research, 2023)
Today, colonizing the neighborhood is more accessible to the everyday individual than ever before with the widespread accessibility and popularity of hyper-local digital platforms like Nextdoor. Our project investigates how individuals use these platforms to better understand how their colonial practices are reshaped and perpetuated in the era of the networked smart home. Through a content analysis of user-generated posts in West Philadelphia, we find that users rarely engage with explicitly racist language or topics. Rather than interpret this finding as an indication that Nextdoor users are not racist, or that the platform’s content moderation strategies prevent racism, we argue that users, instead, rely on postracial practices to simultaneously normalize and obscure anti-Blackness. Drawing from Mukherjee et al.’s (2019) concept of “postrace,” we find that users commonly engage in three practices. First, users increasingly shifted away from explicit racial identifiers to more general "race-neutral" goals of safety and community. Second, users shied away from using problematic but non-explicit racialized language (e.g., "thugs"), opting to embed their racializing opinions in broader “policy” discussions. Third, even with increased attention on the harms of surveillance technologies on people of color, discussions around monitoring remained relatively consistent. These themes reflect postracial racism as yet another iteration of colonization in the neighborhood, entrenching essentializing tactics, perpetuating carceral logics, and developing and perfecting surveillance through the site of Blackness.